2018
DOI: 10.1080/03004430.2018.1471074
|View full text |Cite
|
Sign up to set email alerts
|

‘A different kind of normal’: parents’ experiences of early care and education for young children born prematurely

Abstract: The number of preterm births is increasing globally and in England, yet professional knowledge about the short and long-term developmental consequences and the psycho-social effect on parents is limited amongst the early years workforce. Using a social ecological systems theory approach this paper reports on a mixed-methods study that aimed to explore parents' experiences of early care and education for young children born prematurely.Findings suggest that having a baby born prematurely has the potential to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…In relation to parents' experiences of premature birth, parents in this study reported feeling unprepared for the eventuality of premature birth and that both this and the paucity of information provided to them in hospital had the potential to affect parents' emotional state and their relationship with their infant. Preparing all parents for the possibility of premature birth might help to reduce some of the stress and prolonged psychological distress created by an unknown reality that parents felt ill-prepared for as noted by previous research (Blackburn and Harvey, 2018;Meck et al, 1995;Carson et al, 2015;Treyvaid et al, 2014). In addition, some parents reported their hospital experience in negative terms contributing to the overall traumatic experience of having a child born prematurely.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In relation to parents' experiences of premature birth, parents in this study reported feeling unprepared for the eventuality of premature birth and that both this and the paucity of information provided to them in hospital had the potential to affect parents' emotional state and their relationship with their infant. Preparing all parents for the possibility of premature birth might help to reduce some of the stress and prolonged psychological distress created by an unknown reality that parents felt ill-prepared for as noted by previous research (Blackburn and Harvey, 2018;Meck et al, 1995;Carson et al, 2015;Treyvaid et al, 2014). In addition, some parents reported their hospital experience in negative terms contributing to the overall traumatic experience of having a child born prematurely.…”
Section: Discussionmentioning
confidence: 97%
“…The survey questions were piloted with three parents prior to launch. This paper reports only on the early postnatal and community support and intervention data as the early care and education data has been reported elsewhere (Blackburn and Harvey, 2018). The link to the survey was placed on the University website and the survey was promoted widely through existing links and social media.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Blackburn and Harvey (2020) recently found that British parents of preterm children feel that early years practitioners (i.e., educators of children from birth to 5 years) lack understanding and awareness of their children's specific needs and consequently do not individually adapt their teaching strategies. Accordingly, researchers suggest that teachers should receive training about the potential needs of preterm children and how best to communicate with their parents [37,38].…”
Section: Introductionmentioning
confidence: 99%